Optimal deployment for carbon capture enables more than half of China’s coal-fired power plant to achieve low-carbon transformation - Lin Yang; Ning Wei; Haodong Lv; Xian Zhang (iScience, 2022)
Summary: Carbon capture, utilization and storage (CCUS) technology is critical to global net-zero emission goal, whereas actual deployment is well below expectations. This study constructs a comprehensive framework, integrating nonlinear dynamic optimization, real option and technology learning curve, to explore optimal CCUS deployment for China’s coal-fired power plant toward carbon neutrality. The commercialization application will occur in 2030–2035, with the optimal potential ranging between 248.54 GW and 564.90 GW. East China has the greatest potential, reaching 196.85 GW, followed by North China with the potential of 116.29 GW. The cost of second-generation capture technology will decrease from 219 CNY/ton CO2 to 165 CNY/ton CO2 during 2030–2031.The annual corporate expenditure (R&D investment and capture cost) and government expenditure (subsidy) will peak at 23.92 billion CNY in 2035 and 63.71 billion CNY in 2044, respectively. The financial burden can be lessened by carbon trading market and third-party intervention in the later period.